PENERAPAN EDUTAIMENT POLA ASUH ANAK SEBAGAI PENDIDIKAN KARAKTER PADA KELUARGA MISKIN - Daryati, Melia Eka; Sari , Julia Purnama (Jurnal Abdi Insani, 2024)
This community service activity aims to apply the concept of edutainment in childcare as an effort to educate character in poor families. Edutainment is a combination of education and entertainment, expected to be an effective method in educating children's character in underprivileged family environments. The implementation of community service is carried out for parents in Rawa Makmur Village who are included in the data of 28 hopeful family recipients. The methods used include developing materials and forming caregiver groups. The stages of community service are carried out through preparation of activities carried out because of the program family capacity improvement meeting, implementing technical assistance activities in the form of education in the form of counseling and mentoring, and reporting activities. The results of community service are expected to show an increase in parents' understanding of the importance of character education, positive changes in childcare patterns, and better development of children's character in poor family environments. The sustainability of community service activities through the formation of a community of parents who care about children's character education, providing edutainment materials that can be accessed sustainably, and collaborating with educational institutions and local governments to support this program in the long term.